Coach in the Spotlight - Hay, G. (2014 Coaches Conference - Rio, Brazil, 2014)
Presentations of the author on the 2014 FISA Coaches Conference which was held in Noveber 2014 in Rio, Brazil. He presents his philosophy of coaching which consits of the following key points: structured programme, hard work, individualising sessions, good intensity, keeping it simple, expert coaching, creating self belief, optimism not Pessimism, emotions are contagious, quickly identify the best way your athlete learn, communication, trust, you need to care about your athlete, short and long term preparation, seeking feedback and acting on it, constant reviewing performance and training, being focused only on coaching, ignoring outside distractions,opposition analysis/race strategy and tactics, let athletes know what is occurring, explaining to them why or why not, treat each athlete as an individual, good recovery during and between sessions. He tells about technique, the NZLcentralised programme, key points to success, he explains, why rowing in NZL is strong and other points making rowing NZL so successful.